Incremental space-time block codes with error protection for cooperative relay networks - James, Ashish. (2013)
In cooperative networks, processing at the forwarding nodes is a major source of error propagation. In this context, a novel spectrally efficient distributed space-time block coded (STBC) transmission scheme with error protection for such networks is proposed. The proposed scheme retains the spatial diversity and enhances the bandwidth efficiency by integrating incremental redundancy techniques into such cooperative systems. The guard against error propagation is provided by cooperatively transmitting the additional redundancy bits in an STBC fashion. Theoretical framework is also developed for the proposed system to provide an understanding on the impact and severity of error propagation, and to characterize the fundamental performance of such practical cooperative relay networks.